Overcomer [videorecording (DVD)] - Kendrick, Alex, 1970-; Kendrick, Alex, 1970-; Kendrick, Alex, 1970-; Wright-Thompson, Aryn; Shirer, Priscilla, 1974-; Davies, Ben, 1989- (Sony Pictures Home Entertainment, 2019)
After his team is reduced to nothing when the largest manufacturing plant in town suddenly shuts down, a high school basketball coach mentors a struggling student in cross country.